Stratifying risk in the prevention of recurrent variceal hemorrhage: Results of an individual patient meta‐analysis. Issue 4 (26th August 2017) - Albillos, Agustín; Zamora, Javier; Martínez, Javier; Arroyo, David; Ahmad, Irfan; De‐la‐Peña, Joaquin; Garcia‐Pagán, Juan‐Carlos; Lo, Gin‐Ho; Sarin, Shiv; Sharma, Barjesh; Abraldes, Juan G.; Bosch, Jaime; et al.
Abstract : Endoscopic variceal ligation plus beta‐blockers (EVL+BB) is currently recommended for variceal rebleeding prophylaxis, a recommendation that extends to all patients with cirrhosis with previous variceal bleeding irrespective of prognostic stage. Individualizing patient care is relevant, and in published studies on variceal rebleeding prophylaxis, there is a lack of information regarding response to therapy by prognostic stage. This study aimed at comparing EVL plus BB with monotherapy (EVL or BB) on all‐source rebleeding and mortality in patients with cirrhosis and previous variceal bleeding stratified by cirrhosis severity (Child A versus B/C) by means of individual time‐to‐event patient data meta‐analysis from randomized controlled trials. The study used individual data on 389 patients from three trials comparing EVL plus BB versus BB and 416 patients from four trials comparing EVL plus BB versus EVL. Compared with BB alone, EVL plus BB reduced overall rebleeding in Child A (incidence rate ratio 0.40; 95% confidence interval, 0.18‐0.89; P = 0.025) but not in Child B/C, without differences in mortality. The effect of EVL on rebleeding was different according to Child ( P for interaction <0.001). Conversely, compared with EVL, EVL plus BB reduced rebleeding in both Child A and B/C, with a significant reduction in mortality in Child B/C (incidence rate ratio 0.46; 95% confidence interval, 0.25‐0.85; P = 0.013). Conclusion: Outcomes of therapies to prevent variceal rebleeding differ depending on cirrhosis severity: in patients with preserved liver function (Child A), combination therapy is recommended because it is more effective in preventing rebleeding, without modifying survival, while in patients with advanced liver failure (Child B/C), EVL alone carries an increased risk of rebleeding and death compared with combination therapy, underlining that BB is the key element of combination therapy. (Hepatology 2017;66:1219‐1231).